Devotion and Development: Religiosity, Education, and Economic Progress in 19th-Century France - Mara P. Squicciarini (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper uses a historical setting to study when religion can be a barrier to the diffusion of knowledge and economic development, and through which mechanism. I focus on 19th-century Catholicism and analyze a crucial phase of modern economic growth, the Second Industrial Revolution (1870-1914) in France. In this period, technology became skill-intensive, leading to the introduction of technical education in primary schools. At the same time, the Catholic Church was promoting a particularly antiscientific program and opposed the adoption of a technical curriculum. Using data collected from primary and secondary sources, I exploit preexisting variation in the intensity of Catholicism (i.e., religiosity) among French districts and cantons. I show that, despite a stable spatial distribution of religiosity over time, more religious locations had lower economic development only during the Second Industrial Revolution, but not before. Schooling appears to be the key mechanism: more religious areas saw a slower introduction of the technical curriculum and instead a push for religious education. Religious education, in turn, was negatively associated with industrial development about 10 to15 years later, when school-aged children entered the labor market, and this negative relationship was more pronounced in skill-intensive industrial sectors.
Keywords: J24; N13; Z12; 330; human capital; religiosity; industrialization